2021
DOI: 10.1002/ppul.25581
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for first nonscheduled hospital admissions of pediatric patients on home mechanical ventilation

Abstract: Objectives The number of children on home mechanical ventilation (HMV) has increased. Understanding the reasons for nonscheduled hospital admissions during HMV is critical. This study aims to investigate the risk factors of first nonscheduled hospital admissions of pediatric patients on HMV. Methods A retrospective analysis of patients on HMV between May 1, 2014 and October 1, 2020 was performed. Patients' demographic characteristics, duration of the education of the primary caregiver; time of first nonschedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The potential risks in children on HMV include ventilator failure, airway obstruction by secretion, tracheostomy-related complications (accidental decannulation, bleeding, infection, etc. ), acute lower respiratory tract infection, feeding problems, seizures, dehydration, and electrolyte imbalance [ 78 , 79 ]. A retrospective study reported that children with invasive mechanical ventilation were 16 times more likely to visit hospitals before scheduled visits than children with NIV (odds ratio, 16.3; 95% confidence interval, 2.1–127.4, p =0.008) [ 78 ].…”
Section: Potential Risks Of Home Mechanical Ventilationmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential risks in children on HMV include ventilator failure, airway obstruction by secretion, tracheostomy-related complications (accidental decannulation, bleeding, infection, etc. ), acute lower respiratory tract infection, feeding problems, seizures, dehydration, and electrolyte imbalance [ 78 , 79 ]. A retrospective study reported that children with invasive mechanical ventilation were 16 times more likely to visit hospitals before scheduled visits than children with NIV (odds ratio, 16.3; 95% confidence interval, 2.1–127.4, p =0.008) [ 78 ].…”
Section: Potential Risks Of Home Mechanical Ventilationmentioning
confidence: 99%
“…), acute lower respiratory tract infection, feeding problems, seizures, dehydration, and electrolyte imbalance [ 78 , 79 ]. A retrospective study reported that children with invasive mechanical ventilation were 16 times more likely to visit hospitals before scheduled visits than children with NIV (odds ratio, 16.3; 95% confidence interval, 2.1–127.4, p =0.008) [ 78 ]. Other risk factors for unscheduled hospital admissions were a shorter duration of caregiver education before discharge, a change in the management of the child within 7 days before discharge, and younger age [ 78 - 80 ].…”
Section: Potential Risks Of Home Mechanical Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, Ozcan et al 2 completed a retrospective analysis analyzing risk factors for nonscheduled hospital admissions of pediatric patients on home mechanical ventilation in Turkey. They included pediatric patients hospitalized and initialized on home mechanical ventilation between May 1, 2014 and October 1, 2020.…”
Section: Home Ventilationmentioning
confidence: 99%
“…Second, Ozcan et al 2 Monitoring and timely adjustment of support is key in successfully managing patients supported using chronic mechanical ventilation. Telemedicine is a new modality that may help us with this long-term management.…”
Section: Home Ventilationmentioning
confidence: 99%